Recommendations on Off-Label Drug Use in Pediatric Guidelines - Min Meng; Min Meng; Min Meng; Min Meng; Qi Zhou; Qi Zhou; Wenjuan Lei; Min Tian; Ping Wang; Ping Wang; Yunlan Liu; Yajia Sun; et al. (Frontiers Media S.A., 2022)
Objective: To systematically analyze the supporting evidence, drug information, and the type of off-label drug use in recommendations on off-label drug use in pediatric guidelines.Methods: A cross-sectional study was performed by systematic search through MEDLINE (via PubMed) and Embase databases to identify literature published from 1 January 2018, to 31 December 2020. Only pediatric clinical practice guidelines that included recommendations on off-label use of drugs were included. We present descriptive information on the sources of the included guidelines, country, publication year, evidence grading system used, details on the types of off-label drug use, and the types of studies used as references to support the recommendations.Results: A total of 66 pediatric guidelines with 605 recommendations were included. Eighty-seven (14.4%) recommendations did not cite any references; and the remaining 518 recommendations were supported by 2,240 references (mean 4.3 references/recommendation). The most common types of studies cited were pediatric RCTs (n = 314, 14.0%), pediatric case series studies (n = 260, 11.6%), and reviews (n = 255, 11.4%). Twenty-one percent (n = 470) of the references were studies on adults. One hundred and forty (23.1%) recommendations were graded using the Grading of Recommendations, Assessments, Development, and Evaluations (GRADE) system, of which 37 (26.4%) were graded as strong but supported with only C or D level of evidence. The most commonly reported type of information in the recommendations was indication (n = 499, 82.5%). The most commonly addressed type of off-label drug use in the 523 positive recommendations was unapproved population (n = 255, 48.8%). Sixty-nine (11.4%) recommendations explicitly reported the drug use as off-label.Conclusion: Children may be exposed to medical risks due to gaps in reporting and evidence of off-label drug use recommendations in pediatric guidelines.